Anticonvulsants and thyroid function. Issue 6127 (17th June 1978) - Yeo, P P; Bates, D; Howe, J G; Ratcliffe, W A; Schardt, C W; Heath, A; Evered, D C
Abstract : Serum total and free thyroid hormone concentrations were estimated in 42 patients with epilepsy taking anticonvulsants (phenytoin, phenobarbitone, and carbamazepine either singly or in combination). There was a significant reduction in total thyroxine (TT4), free thyroxine (FT4), and free triiodothyronine (FT3) in the treated group compared with controls. Free hormone concentrations were lower than total hormone concentrations, suggesting that increased clearance of thyroid hormones occurs in patients receiving anticonvulsants. Detailed analysis indicated that phenytoin had a significant depressant effect on TT4, FT4, FT3, and reverse T3 (rT3). Phenobarbitone and carbamazepine had no significant main effects, but there were significant interactions between phenytoin and carbamazepine for TT4 and FT4. phenobarbitone and carbamazepine for FT3, and phenytoin and phenobarbitone for rT3.